PELATIHAN PAJAK UMKM DAN E-PAJAK, SERTA STARTEGI INVESTASI BAGI GEN Z DI SMK TRISAKTI JAYA KOTA BANDAR LAMPUNG - Rizki, Marsi Fella; Ameraldo, Fedi; Sari, Tri Darma Rosmala; Ardiansyah, Diki; Ambarwati, Putri; Ramadhani, Diah (COMMENT: Journal of Community Empowerment, 2024)
Community service activities carried out on tax training for Micro, Small and Medium Enterprises (MSMEs) as well as the introduction of e-taxes and investment strategies for Generation Z at SMK Trisakti Jaya, Bandar Lampung City. In the context of the development of the digital economy, understanding taxes and investment is very important to prepare the younger generation for future challenges. This training aims to provide basic knowledge about tax obligations, the benefits of e-tax, and ways to invest smartly. The community service activities carried out were successful, as evidenced by the participants' enthusiasm for the training. Participants showed activeness in asking questions about the material presented